3x+6=5x+1

Simple and best practice solution for 3x+6=5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=5x+1 equation:


Simplifying
3x + 6 = 5x + 1

Reorder the terms:
6 + 3x = 5x + 1

Reorder the terms:
6 + 3x = 1 + 5x

Solving
6 + 3x = 1 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + 3x + -5x = 1 + 5x + -5x

Combine like terms: 3x + -5x = -2x
6 + -2x = 1 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + -2x = 1 + 0
6 + -2x = 1

Add '-6' to each side of the equation.
6 + -6 + -2x = 1 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 1 + -6
-2x = 1 + -6

Combine like terms: 1 + -6 = -5
-2x = -5

Divide each side by '-2'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| -12+6z=-66 | | 9x/5-11/3=-9/7-x | | 4t-2=2 | | -(-14x+25)-21-19x=23x+20 | | 27+7z=-6z+28z-23 | | 2x^2-20x-48=0 | | -8(y-7)=4y-40 | | -5y/4-6/5=7/3 | | 4r^2+24r=-17 | | -5(2x+3)=15 | | .18-.33= | | 2x^2-19x-6=0 | | 4x^3-16x^2-9x-36=0 | | -5(3z+3)=-3(5z-4) | | 3+3y/2=7/2 | | 1/5x+2/3=-4/5x-1/6 | | 5(2g-3)-6g=-2(g-6)+3 | | 3x^2-45x+4x-60=0 | | 2x^2+4x=9x-18 | | 9x+12=48 | | 12=m/7+3 | | 4(8x+6)=-7(3x-4)+5x | | 30=3(w-5)+6w | | 6Z/5+7=0 | | x+3x+3=9 | | 5(y+4)-8y=17 | | -s+3=5a | | -4/3+Y=0 | | Y=70-1 | | -3(t+5)+(4t+2-4)=8 | | -2u+4(u-2)=-12 | | u/2-5=-9 |

Equations solver categories